Analysis on distribution IS431 and IS1272 in Methicillin Resistance and Susceptible Coagulase-negative Staphylococci (CoNS) among carriage - Edna Primus (2016., 2016)
Insertion sequences (IS) were segments of bacterial DNA, which were also known as transposable elements. Insertion sequences such as IS431 and IS1272 were widely distributed in Staphylococci species. These elements were located at the mec complex together with the mecA, which encodes the penicillin-binding protein 2a that contributed the resistance to beta-lactams antibiotic, including methicillin. However. mecA gene usually exists in Methicillin Resistant Coagulase-negative Staphylococcus (MRCoNS) but not in Methicillin Susceptible Coagulase-negative Staphylococcus (MSCoNS). Furthermore, the existing of nzec complex is not determined by mecA gene only, since the previous studies have shown the existing of IS431 and IS1272 in MS-CONS without mecA. To determine the distribution of the IS431 and IS1272 in MRCoNS and MS-CONS among carriage. To observe the genetic status of IS431 and IS1272 of carriage isolates of CoNS from the Staphylococci species presence in the IS Finder and NCBI. 122 CoNS from our collection were cultured on the MannitoI Salt Agar (MSA). Next, boiling method was used to disperse bacteria to release DNA. The supernatant from boiling were used for IS431 and IS1272 amplification using the Thermocycler PCR machine. Previous primers of IS431 and IS1272 that were described by Kobayashi et al., (1999) were used to amplify. the desired genes. The presence of amplified PCR product of IS431 and IS1272 were ascertained by electrophoresis on I% agarose gel for 65 minutes at 70V and observe under the Trans UV illuminator. Then, the selected CoNS were sent for sequencing. The data collected were analyzed by using SPSS software. Fisher's Exact Test was employed to evaluate the significance level of the IS431 and IS1272 with the mecA. Then phylogenetic trees were constructed for both IS431 and 1S1272. 97.3% of mecA negative CoNS have IS431 and 100% of mecA positive CoNS have IS431. Only, 3.6% of mecA negative CoNS showed positive in IS1272, while mecA positive CoNS showed higher percentage of IS1272, which was 50%. Fisher's Exact test showed that there were significant association between IS1272 and mecA but no significant association between IS431 and mecA. Both of IS431 and IS1272 between isolate CoNS and CoNS in the IS Finder and NCBI were closely related to each other. The presence of IS431 was highly distributed in both MSCoNS and MRCoNS as compared to IS 1272.
Project paper (B.S.(Biomedical Sciences)) - Universiti Putra Malaysia, 2016.